Yield, physico-chemical and nutritional characteristics of MR219 rice mutants and their effects on glycemic index and responses in Balb/c mice - Kadar, Asma Ilyani (2018)
Rice is the most important food in Malaysia. Large efforts have been undertaken towards new variety development, technology improvement and innovation. Mutation technique is a conventional breeding method and it is very effective in improvement of main crop characteristics such as yield traits, resistance to diseases and pests and nutritional qualities. The continuous increase in rice consumption on daily basis due to increase in human population causes health related issues among diabetic’s patients. As the awareness of the general public as related to healthy food increases, diabetic patients are constantly in search of rice variety suitable for their diet. Thus, this study was undertaken to determine the genetic variations among quantitative traits such as physic-chemical, nutritional and yield characteristics of MR219 mutant lines and their glycemic responses in relation to diabetic conditions. In this study, MR219 seeds were treated with carbon ion radiation (60 Gray) by AVF-Cyclotron at the National Institute of Quantum and Radiological Science and Technology (QST), Japan and were planted at the Malaysian Nuclear Agency up to forth mutant generation (M4). Thirty-one M4 mutant lines (ML1 to ML31) were evaluated on vegetative, yield and yield components, physico-chemical characteristics and nutritional composition in comparison with the parental variety, MR219. Analysis of variance revealed that there was a significant difference among the mutant lines in culm height, days to flowering, number of tillers, number of panicles, 1000-grain weight, total grain weight, moisture content, total of dry matter, alkaline spreading value, gel consistency, amylose content, ash, protein, fat, dietary fibre, carbohydrate and energy. Mutant line ML21 had the best performance in majority of yield components and vegetative traits as compared to other mutant lines and parental variety. For nutritional composition, mutant lines namely ML31, ML21, ML10, ML19 were improved in crude protein content, dietary fibre and carbohydrate content. The phenotypic coefficient of variation of vegetative, yield and yield components were found higher than their genotypic coefficient of variation. These indicated great environmental effects in this population. The estimation of glycemic index revealed two mutant lines namely ML3 and ML30 had significantly lower glucose reading (5.49mmol/L and 5.47mmol/L, respectively) than parental variety and other mutant lines. The normal glucose reading in ML3 and ML30 also resulted in moderate GI values (65% and 66%, respectively) and could be suggested for further breeding programme to develop low GI rice. In this study, ion beam irradiation had significantly induced genetic variability in yield and yield components, physico- chemical characteristics and nutritional composition which also affected the glycemic index of the rice.